Islamic Extremism and CBRN Terrorism - McCann, Wesley S. (Terrorism and political violence, 2023)
The extant literature on the relationship between religious ideology and CBRN weapons pursuit lacks a strong empirical basis. To address this, the current study utilizes a new dataset—the CBRN Terrorism Database (CTD)—to evaluate whether Islamic actors are more or less likely to pursue CBRN weapons. Binary logistic regression models are used on several different constrained subsamples to assess the relationship between ideology, group-, and country-level factors and CBRN weapons pursuit. Across the models, the strongest predictors of pursuit are whether the actor is an individual, is inspired by an Islamic ideology, and resides in a country with low levels of ethnic fractionalization. Other factors are important under specific contexts, but Islamic groups are significantly more likely to pursue CBRN weapons as well. Implications and recommendations are discussed.